2013
DOI: 10.1002/hed.23330
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term functional and survival outcomes after induction chemotherapy and risk‐based definitive therapy for locally advanced squamous cell carcinoma of the head and neck

Abstract: Purpose To evaluate long-term outcomes after induction chemotherapy followed by “risk-based” local therapy for squamous cell carcinoma of the head and neck (SCCHN). Methods Forty-seven patients (stage IV, ≥N2b) were enrolled in a Phase II trial. Baseline and 24-months functional measures included modified barium swallow (MBS) studies, oropharyngeal swallow efficiency (OPSE), and the MD Anderson Dysphagia Inventory (MDADI). Functional status was assessed at 5 years. Results Five-year overall survival was 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 29 publications
7
42
0
1
Order By: Relevance
“…Given the longitudinal, retrospective nature of this study, the potential for underreporting is also of concern. However, it should be noted that median follow-up was 48 months, and 94% of patients were followed for more than two years and though videoflouroscopy was not used routinely creating the potential for missed “silent aspiration,” the 7% rate of chronic aspiration detected by videoflouroscopy in the current study is very close to the 7.6% aspiration rate we previously reported for a group of patients in a prospective institutional organ preservation trial using routine videoflouroscopic dysphagia assessment[33]. Finally, our choice of recursive partitioning analytic methods represents an inherently “greedy” model system, and classification and regression tree approaches often are sensitive to “noise” from random variation within the dataset.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Given the longitudinal, retrospective nature of this study, the potential for underreporting is also of concern. However, it should be noted that median follow-up was 48 months, and 94% of patients were followed for more than two years and though videoflouroscopy was not used routinely creating the potential for missed “silent aspiration,” the 7% rate of chronic aspiration detected by videoflouroscopy in the current study is very close to the 7.6% aspiration rate we previously reported for a group of patients in a prospective institutional organ preservation trial using routine videoflouroscopic dysphagia assessment[33]. Finally, our choice of recursive partitioning analytic methods represents an inherently “greedy” model system, and classification and regression tree approaches often are sensitive to “noise” from random variation within the dataset.…”
Section: Discussionsupporting
confidence: 77%
“…Even in modern practice, up to 60% of patients require feeding tube placement during IMRT[42]. More alarmingly, we previously reported a 7.6% chronic aspiration rate amongst head and neck (primarily oropharyngeal) squamous cell carcinoma patients undergoing chemoradiotherapy[33], and the Michigan group have reported that up to 20% of survivors develop chronic aspiration even with dysphagia-optimized IMRT planned specifically to minimize dose to non-target swallow critical structures including the constrictors and larynx[4345]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] Indeed, it is often the treatment of choice for laryngeal cancers because the functional outcomes are good and seem superior to surgical management. 21,22 Although oncologically effective, radiation to the vocal folds can be associated with functional limitations.…”
Section: Physiopathologymentioning
confidence: 99%
“…These exercise programs are associated with better post-treatment swallowing function, in particular on the short-term [5][6][7][8][9][10], and probably also longer-term [11]. However, since dysphagia can develop and/or progress years after CRT [12,13], long term (10-years+) prospectively collected swallowing and mouth opening data are of great importance to assess deglutition in HNC survivors [14]. In this study the prospectively collected objective and subjective functional results at 10-years+ post-treatment will be reported in a patient cohort treated with CRT for advanced, anatomical and functional inoperable HNC.…”
Section: Introductionmentioning
confidence: 99%